Do pregnant women contact their general practitioner? A register-based comparison of healthcare utilisation of pregnant and non-pregnant women in general practice - Feijen-de Jong, Esther I (BioMed Central, 2013)
BACKGROUND: Midwives and obstetricians are the key providers of care during pregnancy and postpartum. Information about the consultations with a general practitioner (GP) during this period is generally lacking. The aim of this study is to compare consultation rates, diagnoses and GP management of pregnant women with those of non-pregnant women. METHODS: Data were retrieved from the Netherlands Information Network of General Practice (LINH), a nationally representative register. This register holds longitudinal data on consultations, prescriptions and the referrals of all patients listed at 84 practices in the Netherlands in 2007–2009, including 15,123 pregnant women and 102,564 non-pregnant women in the same age-range (15 to 45 years). We compared consultation rates (including all contacts with the practice), diagnoses (ICPC-1 coded), medication prescriptions (coded according to the Anatomical Therapeutic Chemical classification system), and rate and type of referrals from the start of the pregnancy until six weeks postpartum (336 days). RESULTS: Pregnant women contacted their GP on average 3.6 times, compared to 2.2 times for non-pregnant women. The most frequently recorded diagnoses for pregnant women were ‘pregnancy’ and ‘cystitis/urinary infection’, and ‘cystitis/urinary infection’ and ‘general disease not otherwise specified’ for non-pregnant women. The mean number of prescribed medications was lower in pregnant women (2.1 against 4.4). For pregnant women, the most frequent referral indication concerned obstetric care, for non-pregnant women this concerned physiotherapy. CONCLUSIONS: GP consultation rates in pregnancy and postpartum shows that GPs are important providers of care for pregnant women. Therefore, the involvement of GPs in collaborative care during pregnancy and postpartum should be reinforced.